Оптимизация режимов работы котлов ТЭС по критерию минимума энергетических потерь - Мезеря, Андрей Юрьевич (НТУ "ХПИ", 2016)
Поставлена задача оптимизации режимов работы котельного оборудования тепловых электростанций по критерию минимума энергетических потерь и намечены пути её решения. Определены основные технологические параметры и внешние возмущения, оказывающие влияние на величину энергетических потерь в прямоточных котлах ТЭС. Составлена математическая модель задачи оптимизации режимов работы котлов по критерию минимума энергетических потерь.

This scientific paper gives the definition of the formal optimization problem of operating conditions for the equipment of thermal power plants using the criterion of minimum power losses and defines the methods of its solution. The main process parameters and external perturbations that influence the value of power losses in the direct flow boilers of thermal power stations have been defined. The mathematical model of the optimization problem of operating conditions for the equipment of thermal power plants using the criterion of minimum power losses has been constructed.
Optimizing the operating conditions of boilers of thermal power plants using the criterion of minimum power losses
Keywords: тепловая электростанция; энергосбережение; энергосберегающее управление; паровой котёл; системы автоматического управления; thermal power station; power saving; energy saving control